2020
DOI: 10.1159/000508688
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomal Gamma-Glutamyltransferase Activity Increased in Patients with Renal Cell Carcinoma with Advanced Clinicopathological Features

Abstract: Background: There has been no clinically useful diagnostic or prognostic biomarker for renal cell carcinoma (RCC). Serum γ-glutamyltransferase (GGT) activity has been reported to be a prognostic marker for several types of cancer including RCC. Exosomes or small extracellular vesicles present in body fluids have potential as a biomarker. We have recently demonstrated that GGT activity on exosomes isolated from serum is useful for the differential diagnosis of prostate cancer and benign prostate hyperplasia. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Further, its inhibition significantly decreased the migration of tumor cells, suggesting that GGT1 might be of therapeutic interest for patients with renal cancer (24). Another study further revealed that serum exosomal GGT1 could be a useful marker for advanced clinical features of patients with renal cancer (25). Kawakami et al (26) found that the activity of serum exosomal GGT1 was significantly higher in individuals with prostate cancer than those with benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, its inhibition significantly decreased the migration of tumor cells, suggesting that GGT1 might be of therapeutic interest for patients with renal cancer (24). Another study further revealed that serum exosomal GGT1 could be a useful marker for advanced clinical features of patients with renal cancer (25). Kawakami et al (26) found that the activity of serum exosomal GGT1 was significantly higher in individuals with prostate cancer than those with benign prostatic hyperplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, serum GGT combined with other serum biomarkers were effective diagnostic markers of AFP-negative HCC, especially in individuals with early stage, small size or good liver function (42). More researchers continue to assess the prognostic role of serum GGT in cervical cancer (43), esophageal squamous cell carcinoma (44), ovarian cancer (45), renal cell carcinoma (25), and HCC (46). By carrying out a clinical analysis, Zhang et al (15) found that a high concentration of serum GGT was positively associated with advanced TNM stage and large tumor size and was an independent element for predicting the OS rate of patients with primary HCC.…”
Section: A B D Cmentioning
confidence: 99%
“…Serum exosomal GGT activity has recently been reported as superior to serum total GGT activity as a biomarker for predicting the clinicopathological features of patients with RCC [99]. The authors of the study concluded that exosomal GGT reflected the characteristics of the original cancer cells and might indeed predict the likelihood of a microvascular invasion while the total serum GGT activity could not.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…We have previously reported several EV markers in serum and urine that are useful for diagnosis and monitoring of several diseases including PC. [8][9][10][11][12][13][14] EV samples isolated from serum by conventional methods such as sequential centrifugation, polymer-based precipitation, gelfiltration, and immunoaffinity are not suitable for proteomic analysis, because they are heavily contaminated with serum proteins. Recently, a novel affinity-based method was reported in which highly purified EVs are isolated using T-cell immunoglobulin domain and mucin domain-containing protein 4 (hereinafter referred to as Tim4) that recognizes phosphatidylserine (PS) on EVs, allowing us to identify disease-associated proteins in serum EVs.…”
Section: Introductionmentioning
confidence: 99%
“…Since blood can be collected in a less invasive manner, EV markers in blood can be analyzed repeatedly. We have previously reported several EV markers in serum and urine that are useful for diagnosis and monitoring of several diseases including PC 8‐14 …”
Section: Introductionmentioning
confidence: 99%